Prediction of 5-10km performance based on the aerobic-anaerobic threshold - Santos, P.; Novo, L. (2001)
The aerobic-anaerobic threshold (Mader et al. 1976) is a procedure commonly used by researchers to evaluate middle and long-distance running performance. The purpose of this study was to analyse the relationship between aerobic capacity and running performance in 5-10km runners in an attempt to predict their performance. Two groups of athletes were used: G5km, 5000m runners (n=14); G10km, 10000m runners (n=14). Each subject was submitted to an incremental field test (4x2000m) one week before the competition, to determine the running speed at a blood lactate concentration of 4mmol/l (V4). Increments of 0.4m/s and running speeds between 4.2 and 5.8 m/s were used. Capillary blood was taken from the ear lobe in the 30-40s immediately after the conclusion of each step and analysed in a YSI-1500L Sport. Statistical analysis included the independent t-test and the simple linear regression. The significance level was set at 5%. Concerning competition results the G5km achieved an average best time of 14'07" (13'30"-15'12") while the G10km registered 29'42" (28'06"-32'50"). In both groups a high correlation (r=0.90) was found between the V4 and the competition result. No significant mean differences in V4 were found between groups. The r2=80% found in both groups seems to assure high predictions relatively to the performance in this type of competitions. The standard error of estimate was 13s (5km) and 39s (10km), respectively. In conclusion, the margin of error assured by a prediction based in the V4 is reduced in a 5km race and therefore can be of useful applicability. However the margin of error resulting from the same type of prediction in the 10km is much greater and therefore may not represent a helpful tool in competition prognosis.